APAKAH METODE FIFO DAN RATA-RATA MEMANG BERBEDA : Bukti Empiris dari Bursa Efek Jakarta - Syukriy Abdullah; Muslim A. Djalil (Media Riset Akuntansi, Auditing & Informasi, 2004)
The objective of this research is to examine and give the empirical evidence of differences between FIFO (first-in, first-out) and average by inventory variability, firm size, leverage, current ratio, and gross profit margin at manufacture companies that listed at BEJ. By using 65 companies sample (12 FIFO company's and 53 averages company's) which choose by purposively. This research found that no differences between both method. This make advance question, why the company choose FIFO or average method, while both of method are no differences.Keywords: Supply method, supply, variability, company size, leverage, current ratio, gross profd margin.